Pemberdayaan Kelompok Ibu Hamil, Nifas, dan Menyusui dalam 1000 Hari Pertama Kehidupan dengan Demonstrasi Gizi Lengkap dan MP-ASI sesuai Isi Piringku sebagai Upaya Cegah Stunting - Podungge, Yusni; Hikmandayani, Hikmandayani; Igirisa, Yusni; Olii, Nancy; Tompunuh, Magdalena M; Harun, Desrianti; Indriyani, Putry (Jurnal Stunting Pesisir dan Aplikasinya, 2022)
The incidence of short toddlers or commonly referred to as stunting is one of the nutritional problems experienced by toddlers in the world and is a major nutritional problem faced by Indonesia. The first 1000 days of life is a golden period to form a healthy child. One way to prevent stunting is to fulfill nutrition and health services for pregnant women, postpartum mothers and breastfeeding mothers. This community service aims to increase the knowledge of pregnant women, postpartum mothers, breastfeeding mothers and mothers of children under five about nutritional needs and the correct method of processing MP-ASI. Implementation of community service using nutrition education methods, demonstrations of making MP-ASI, and health checks. The average post-test results showed that there was an increase in participants' knowledge after the implementation of community service.